On Multi-Index Mittag–Leffler Function of Several Variables and Fractional Differential Equations. (18th October 2021) - Jaimini, B. B.; Sharma, Manju; Suthar, D. L.; Purohit, S. D.
Abstract : In this paper, we have studied a unified multi-index Mittag–Leffler function of several variables. An integral operator involving this Mittag–Leffler function is defined, and then, certain properties of the operator are established. The fractional differential equations involving the multi-index Mittag–Leffler function of several variables are also solved. Our results are very general, and these unify many known results. Some of the results are concluded at the end of the paper as special cases of our primary results.